GAGASAN TEORI BATAS MUAMMAD SYAHRÃR DAN SIGNIFIKANSINYA BAGI PENGAYAAN ILMU USHUL FIQH - Abidin, M. Zainal (Islamic University of Indonesia, 2006)
This paper tries to elaborate Muhammad Syahrûr thought on the idea of his limit theory and its significant to enrich the ushul fiqh. Without any presedent before, Syahrûr submit six patterns of understanding the verses of holy Quran when speak about law. However, the six models of limit theory submitted by Syahrûr seem to be related with his education background, thats science for he is an engineer. Among the tradition of the Islamic law thought, the Syahrûrs idea is something new and an innovative one. Commonly, it could be understood that through the flexibility of Islamic law as mentioned by the limit theory, Syahrûr purposed to say that the Quran verses always relevant in any situation and condition, and Islam is the last religion and the universal one for all human being. Kata Kunci: hudûd, al-hanîf, al-istiqâmah, al-harakah al-jadâliyah